Strategi Guru dalam Pengembangan Nilai Praktis Sila Ke-5 Pancasila pada Pembelajaran Tematik di Kelas Rendah Sekolah Dasar 121/I Muara Singoan - Dedek Nuranisa; Fadelina Wizola Diva; Puput Tri Rosdianah; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
This study aims to find out and describe how the strategies that teachers can use to develop the practical value of the fifth principle of Pancasila in the thematic learning process for first grade students at SDN 121/I Muara Singoan. This study uses a qualitative research method where data is obtained from observation, interviews and documentation techniques sourced from teachers, students, principals and parents of students. Then the data were analyzed using the data analysis technique of the Miles and Huberman model, namely reduction, presentation and conclusion. This study has the result that the strategies that have been implemented include the PAIKEM strategy, cooperative learning and inquiry, and various lectures to get students to always read, discuss. Other strategies used by teachers in instilling and developing the practical value of Pancasila, especially the principle of "Social Justice for All Indonesian People" in thematic learning in class I SDN 121/I Muara Singoan, namely: 1) Exemplary / examples prove that the teacher has become an example / good role model. good for students, especially in applying a family attitude, balance between rights and obligations, and working hard. 2) Spontaneous activities such as asking for donations to visit sick friends in order to instill a social care attitude. 3). The reprimand strategy is carried out to remind students who violate Pancasila values and school rules, then carry out personal coaching and do not corner students. 4) The strategy through environmental conditioning can also be seen from the availability of infrastructure that supports the implementation of the Pancasila values attitude. 5). The strategy through routine activities is the integration of Pancasila attitudes in learning tools such as lesson plans, starting from the use of learning strategies and techniques that are routinely carried out every day in the thematic learning process.